Acute beetroot juice supplementation augments early neuromuscular performance after blood flow restriction: a crossover study in elite basketball players - Nie, R.; Zhang, G.; Kong, J.; Wang, X.; Xie, Z.; Lin, L.; Li, T.; Liang, Y. (Frontiers in Nutrition, 2026)
Introduction: Beetroot juice (BJ), rich in nitrate, has been shown to enhance exercise performance via nitric oxide-mediated pathways. While its effects on endurance and strength have been studied, its influence on blood flow restriction (BFR)-induced post-activation potentiation (PAP) remains unclear.